Рrospects for the development of retreat tourism in Ukraine - Irina Shamara; Hanna Haponenko; Olena Yevtushenko; Tymur Vygovskyi (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2024)
In order to get more and more satisfaction from life, people began to turn more and more often to various types of self-knowledge, using not only scientific methods. Thus, a phenomenon has appeared in society that has become to some extent a "spiritual" trend and is the root of all world spiritual and physical practices, which includes various types of meditation - this is "retreat tourism", which implies a combination of various spiritual and physical practices in places remote from society, as a rule, where means of communication are not used. Now this direction is rapidly developing and becoming more and more relevant. Retreat tourism is a specific type of travel aimed at restoring mental and physical health, as well as enjoying the beauty of nature and cultural heritage. Ukraine, which is endowed with a variety of natural beauty and historical heritage, has the potential for the development of retreat tourism. However, to date, this direction of tourist activity in Ukraine has not received sufficient attention and consideration in scientific research. The article highlights the peculiarities of the organization of travel retreats, trends, problems and prospects for the development of retreat tourism in Ukraine in modern conditions. The main regions of the world for health tourism and retreat tourism, the types of retreats and the natural potential for the organization of travel retreats in Ukraine are analyzed. The prospects for the development of retreat tourism in Ukraine and aspects of the positive impact of retreat tourism on human psychological health are revealed. The subject of the study is the analysis of the current state, problems and prospects of the development of retro-tourism in Ukraine. The purpose of the study is to determine retreat tourism as a promising direction for the development of tourism in Ukraine. General scientific research methods are used: systematic, descriptive, comparative and structural-logical analysis. During the study, the following results were obtained: the main trends, problems and prospects for the development of retreat tourism in Ukraine were revealed. Conclusions: the feasibility of the development of retreat tourism in Ukraine and the development of the necessary infrastructure for this type of tourism in order to maximize the tourist potential of the country and create a favorable environment for meeting the needs and expectations of the target audience of customers for this type of tourism are substantiated